Faith-Based Diplomacy: The Influence of Indonesian Religious Sentiment on the Palestine Policy Agenda (Palestine Issues on Indonesian Society, 2025)
This paper explores the role of religious sentiment in shaping Indonesia’s foreign policy toward Palestine, focusing on the influence of Islamic faith-based diplomacy. Indonesia, as the largest Muslim-majority country, has long been a vocal supporter of Palestinian self-determination, and this study seeks to examine how religious sentiment shapes this diplomatic stance. The research investigates how religious organizations, political parties, and civil society groups use religious rhetoric and theological principles to advocate for Palestinian rights within the Indonesian policy framework. The paper also examines how faith-based diplomacy in Indonesia operates both domestically and internationally, including the ways in which Indonesia’s Muslim-majority population pressures the government to take a more active role in Palestinian advocacy. Furthermore, it discusses the challenges and opportunities that arise from the intersection of religious sentiment and national political interests in shaping Indonesia's foreign policy on Palestine. The paper contributes to the understanding of how religious ideologies influence state diplomacy, particularly in a Muslim-majority country with a significant role in regional and global politics.